The Strategy of World Uyghur Congress (WUC) to Strive for Human Rights for Uyghur people - Ismah Rustam; Arida Meilani (Resolusi: Jurnal Sosial Politik, 2021)
The World Uyghur Congress (WUC) is a diaspora of ethnic Uyghurs as well as a Non-Governmental Organization (NGO) which aims to realize human rights for Uyghurs ethnic, as one of the ethnic Muslim minorities in China. Thus, in this thesis the authors aim to examine the strategies used by the WUC to fight for human rights for Uyghurs ethnic. In conducting the research, the authors use qualitative research methods that emphasize the presentation of events descriptively and data collection using library research or literature studies, then the data sorted according to research needs. The authors were also assisted with the use of the concepts of NGO, Human Rights and Diaspora to answer the research questions of this thesis. In the end, the authors emphasis that the strategy used by WUC was divided into two, a nonviolent strategy that emphasized the dissemination of information and image of the WUC as a peace organization and lobbying western countries, such as Europe and the United States to get a support.